Preferences and Avoidance of Sleeping Positions Among Patients With Chronic Low Back Pain: A Cross-Sectional Study - Ylinen, Jari; Häkkinen, Arja; Kautiainen, Hannu; Multanen, Juhani (Curēus (Palo Alto, CA), 2024)
Background Chronic low back pain (CLBP) is a common issue among the working-age population. Sleeping position may affect CLBP, with the prone position commonly suggested to be avoided. This study aims to examine the relationship between preferred and avoided sleeping positions and to explore the frequency of increased pain in various sleeping positions among patients with nonspecific CLBP and pain and disability levels. Methods This cross-sectional study included all adult patients referred for specialist consultation for CLBP at the outpatient clinic of the Central Hospital of Central Finland's spine department. Pain intensity was measured using a visual analog scale (VAS), and disability was assessed with the Oswestry Disability Index (ODI). Patients completed a questionnaire detailing the main sleeping positions and positions avoided due to low back pain (LBP). Results The study enrolled 375 consecutive patients, with a mean age of 51 ± 17 years; 64% (n=240) were female. The mean VAS score was 63 ± 24, and the mean Oswestry Index was 38 ± 18%. The majority of patients (87%, n=327) reported sleeping in a side-lying position, followed by supine (47%, n=176) and prone (22%, n=82) positions. A negative correlation was found between age and the preference for sleeping in the prone position. No significant gender differences in sleep positions were observed (p=0.69). Sleep was disturbed in 77% of patients (n=289) due to LBP, and 87% (n=327) reported difficulties due to LBP when getting up. Overall, 92% of participants (n=345) experienced difficulties sleeping or getting up in the morning due to LBP. Many patients avoided certain positions due to pain: 42% (n=157) avoided the prone position, 35% (n=131) the back, 15% (n=56) the left side, and 13% (n=49) the right side. Although the prone position was most commonly linked with pain, especially among women, our findings suggest that any sleeping position could potentially exacerbate pain in individuals with CLBP. Conclusions This study highlights the variability in how sleeping positions affect pain in patients with nonspecific CLBP. While the prone position is most frequently associated with increased pain, individual preferences and responses vary significantly, and often sidelying and supine positions provoke pain. The diversity in sleeping positions that exacerbate pain highlights the need for tailored advice in the management of patients with CLBP.